Validation of a radiosynthesis method and a novel quality control system for [68 Ga]Ga-MAA: is TLC enough to assess radiopharmaceutical quality? - Silvia Migliari; Stefano Bruno; Annalisa Bianchera; Ilaria De Nardis; Antonio Scarano; Monica Lusardi; Anna Gaiani; Alessandra Guercio; Maura Scarlattei; Giorgio Baldari; Ruggero Bettini; Livia Ruffini (SpringerOpen, 2024)
Abstract Background Technetium-99 m-labelled macroaggregated human serum albumin ([99mTc]Tc-MAA) is commonly used for lung perfusion scintigraphy. The European Pharmacopoeia (Eu.Ph.) specifies thin-layer chromatography (TLC) as the only method to assess its radiochemical purity (RCP). Similarly, TLC is the sole method reported in the literature to evaluate the RCP of Gallium-68-labelled MAA [68 Ga]Ga-MAA, recently introduced for lung perfusion PET/CT imaging. Since [68 Ga]Ga-MAA is prepared from commercial kits originally designed for the preparation of [99mTc]Tc-MAA, it is essential to optimize and validate the preparation methods for [68 Ga]Ga-MAA. Results We tested a novel, simplified method for the preparation of [68 Ga]Ga-MAA that does not require organic solvents, prewash or final purification steps to remove radioactive impurities. We assessed the final product using radio-TLC, radio-UV-HPLC, and radio SDS-PAGE. Overall, our quality control (QC) method successfully detected [68 Ga]Ga-MAA along with all potential impurities, including free Ga-68, [68 Ga]Ga-HSA, unlabeled HSA, which may occur during labelling process and HEPES residual, a non-toxic but non-human-approved contaminant, used as buffer solution. We then applied our QC system to [68 Ga]Ga-MAA prepared under different conditions (25°-40°-75°-95 °C), thus defining the optimal temperature for labelling. Scanning Electron Microscopy (SEM) analysis of the products obtained through our novel method confirmed that most [68 Ga]Ga-MAA particles preserved the morphological structure and size distribution of unlabeled MAA, with a particle diameter range of 25-50 μm, assuring diagnostic efficacy. Conclusions We optimized a novel method to prepare [68 Ga]Ga-MAA through a QC system capable of monitoring all impurities of the final products.